EFEKTIFITAS KEPEMIMPINAN KEPALA SEKOLAH STUDI KASUS DI SD NEGERI PERCOBAAN 4 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The research is intended to know the Headmaster competence of SD Negeri Percobaan 4 in terms of the personality, managerial, entrepreneurship, supervision and social dimensions and the efficiency of the Headmaster leadership of SD Negeri Percobaan 4 and to know the problems faced by the Headmaster of SD Negeri Percobaan 4 in carrying out the leadership functions following the solutions. Naturalistic Qualitative Approach is carried out in the research to know the phenomena comprising the data and information naturally without data manipulation. The researcher personally carries out the research in order to know, understand the problem and to describe the research result. The process of data collection is used by the researcher as the key instrument by which the researcher carried out directly, while direct observation is implemented as the technique of data collection in the real condition in the field both physically and non-physically, free but controlled-interview is also implemented in order to achieve the detail and various data, but it is still based on the principles of comparability and reliability from the respondents, the headmaster, the teachers, the parents, the chief of School Committee, the school attendance and the documentation.The result of the research shows that the competence of Headmaster competence of SD Negeri Percobaan 4 in terms of the of personality, managerial, entrepreneurship, supervision and social dimensions already fulfills the Headmaster Competence Standard while the leadership is still ineffective in increasing the test score of National Examination. The problem of fulfilling the leadership efficiency is deal with the input (students) which does not meet the standard ability needed by the school as the school is not allowed to select the candidates based on the required ability. To solve the problem, the school makes some efforts, for example; by giving additional lesson to the students who have not mastered the lesson yet, to the students at the sixth grade, facing theNational Examination, who have not achieved the lesson, improving the teachers’ role for all students, intensifying cooperation with the parents to increase the learning process.